A study on phytochemical properties and antioxidant activity of different solvent extract of Siddha drug Karisalai Karpam chooranam in invitro condition - G, BHARATHKUMAR; M, PITCHIAH KUMAR (Asian Journal of Pharmaceutical and Clinical Research, 2014)
In Siddha system of medicine drugs consist of polyherbal formulations, containing different plants, used for the treatment of various diseases. Karisalai Karpam chooranam is a polyherbal formulation consisting of seven traditionally used herbs since there is no information about pharmaceutical activities of antioxidant and phytochemical evaluation, the present study focused on the in vitro antioxidant methods where different solvent extract of Karisalai Karpam chooranam screened for ABTS free radical scavenging activity, lipid peroxidation assay, superoxide scavenging activity, metal chelating assay, nitric oxide scavenging activity, and Antioxidant activity in hemoglobin induced linoleic acid. The results revealed potent scavenging activity when compared with standard. The aqueous-methanol extract of Karisalai Karpam chooranam was screened for further phytochemicals which indicated the presence of alkaloids, flavonoids, tannin, saponin, tepenoids, polyphenols and absence of glycosides, anthocyanin. These metabolites profile was recorded with thin layer chromatography. The result indicated promising antioxidant activity of crude extract and needs further exploration for their effective use in both modern and traditional system of medicines.